Effects of sodium bicarbonate ingestion on swim performance in youth athletes - Zajac, Adam; Cholewa, Jaroslaw; Poprzecki, Stanislaw; Waskiewicz, Zbigniew; Langfort, Jozef (Journal of sports science & medicine, 2009)
The purpose of this study was to evaluate the effect of oral administration of sodium bicarbonate (300 mg·kg(-1) b.w.) on swim performance in competitive, (training experience of 6.6 ± 0.6 years) youth, (15.1 ± 0.6 years) male swimmers. The subjects completed a test trial, in a double blind fashion, on separate days, consisting of 4 x 50m front crawl swims with a 1(st) minute passive rest interval twice, on two occasions: after ingestion of bicarbonate or placebo, 72 hours apart, at the same time of the day. Blood samples were drawn from the finger tip three times during each trial; upon arrival to the laboratory, 60 min after ingestion of placebo or the sodium bicarbonate solution and after the 4 x 50m test, during the 1st min of recovery. Plasma lactate concentration, blood pH, standard bicarbonate and base excess were evaluated. The total time of the 4 x 50 m test trial improved from 1.54.28 to 1.52.85s, while statistically significant changes in swimming speed were recorded only during the first 50m sprint (1.92 vs. 1.97 m·s(-1), p < 0.05). Resting blood concentration of HCO(-) 3 increased following the ingestion of sodium bicarbonate from 25.13 to 28.49 mM (p < 0.05). Sodium bicarbonate intake had a statistically significant effect on resting blood pH (7.33 vs. 7.41, p < .05) as well as on post exercise plasma lactate concentration (11.27 vs. 13.06 mM, p < 0.05)). Collectively, these data demonstrate that the ingestion of sodium bicarbonate in youth athletes is an effective buffer during high intensity interval swimming and suggest that such a procedure can be used in youth athletes to increase training intensity as well as swimming performance in competition at distances from 50 to 200 m. Key pointsSodium bicarbonate is an effective ergogenic aid, also in youth athletes.Sodium bicarbonate intake improves swimming sprint performance.Sodium bicarbonate intake increases resting blood pH and bicarbonate level.